How to study the postgraduate in communications studies of Ibero-America. The approaches and their political implications - Magalhães Firmino, Leonardo (2017)
This essay seeks to develop a critical view on how the communication studies are taught in the master's degree in Ibero-America. The questions that guided this study were: what kind of researcher or professional of communication studies are being formed? How communication can influence society and culture promoting changes? In this way, we defined what is a curriculum and a master's degree, and finally we told about the three philosophical lines that mostly represent the Ibero-American communication studies’ frame. Concretely, they are the line of communicology, the line of social sciences and the line of cultural studies. We concluded the work pointing out the dangers of using an atheoretical approach.